1996
DOI: 10.1172/jci118603
|View full text |Cite
|
Sign up to set email alerts
|

CD40 expression by human peripheral blood eosinophils.

Abstract: In this study, we have investigated CD40 expression in human peripheral blood eosinophils and in human chronically inflamed nasal tissues, i.e., nasal polyps. We show by both reverse transcriptase-PCR and Northern blot analysis that eosinophils from allergic subjects express human CD40 mRNA. We also show that constitutive CD40 mRNA expression in eosinophils could be upregulated by exposure to IgA immune complexes and downregulated by IL-10 and the synthetic steroid budesonide. In addition, we demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
0
3

Year Published

1997
1997
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(95 citation statements)
references
References 33 publications
(27 reference statements)
7
85
0
3
Order By: Relevance
“…1,6,7 Despite their important role in the pathophysiology of allergy, the precise mechanisms by which eosinophils escape spontaneous apoptosis in allergic disorders have not been completely elucidated. In the present study we confirmed a previous report by Ohkawara et al 16 that eosinophils may express CD40 and that CD40 activation delays eosinophil apoptosis as potently as GM-CSF stimulation. We also demonstrated that CD40 mediates enhancement of eosinophil survival at least partly through induction of C-IAP2 expression and provided in vivo evidence that CD40-mediated C-IAP2 expression occurs in eosinophils at the site of allergic inflammation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…1,6,7 Despite their important role in the pathophysiology of allergy, the precise mechanisms by which eosinophils escape spontaneous apoptosis in allergic disorders have not been completely elucidated. In the present study we confirmed a previous report by Ohkawara et al 16 that eosinophils may express CD40 and that CD40 activation delays eosinophil apoptosis as potently as GM-CSF stimulation. We also demonstrated that CD40 mediates enhancement of eosinophil survival at least partly through induction of C-IAP2 expression and provided in vivo evidence that CD40-mediated C-IAP2 expression occurs in eosinophils at the site of allergic inflammation.…”
Section: Discussionsupporting
confidence: 93%
“…16,19,20 Blood eosinophils and neutrophils have been cultured in the presence of these compounds for 24 or 48 hours before being assayed for CD40 expression to determine whether they affect CD40 expression in granulocytes. Neither IFN-γ (10 µg/mL), GM-CSF (500 U/mL), nor IgA-Ic induced CD40 expression in neutrophils, as determined by means of immunoblotting (Fig 1, A) and flow cytometry (data not shown).…”
Section: Eosinophils Spontaneously Express Cd40 When Culturedmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, IL-10 was shown to down-regulate CD40 mRNA synthesis in eosinophils (4). Because Th1 cytokines such as IFN-␥ are prominent in tuberculoid lesions, and Th2 cytokines such as IL-10 are predominant in lepromatous lesions (34, 3.…”
Section: Regulation Of Cd40 Expression On Monocytesmentioning
confidence: 99%
“…CD40 is a 50-kDa glycoprotein present on the surface of B cells (1), monocytes (2), dendritic cells (3), eosinophils (4), and endothelial cells (5) and is a member of the TNF receptor superfamily (6,7). The expression of CD40 on monocytes has been shown to be up-regulated by IFN-␥, GM-CSF, and IL-3 (2).…”
mentioning
confidence: 99%